Multi-stage Frequency Control of a Microgrid in the Presence of Renewable Energy Units. Issue 2 (20th January 2017) - Ameli, Hossein; Ameli, Mohammad Taghi; Hosseinian, Seyed Hossein
Abstract: The integration of distributed generations such as photovoltaic and wind as well as large load variations leads to the significant issue of frequency stability problem. This paper presents a multi-stage frequency control for microgrids. Energy storage systems such as BESSs are selected as a flexible and fast-response device for this application. In the first stage, a PI control method based on PSO for the BESS is applied in order to minimize the frequency deviations. Moreover, in contingency modes, in which the BESS with the optimized PI control application cannot stabilize the system due to the unbalanced situation of supply and demand, fast reaction of the central control system operator is necessary in order to protect the network from collapse. Hence, in the second stage of the control, a Fuzzy-logic frequency controller as a smart controller is designed. This controller proposes solutions through power level change such as load shedding in a short time to rescue the network from instability. The proposed method is validated by a set of simulations on a representative microgrid. The effectiveness of the proposed multi-stage control is illustrated through the comparison to the one-stage controller without the Fuzzy-logic part.